VD_FINDINFO Jug / 2023 / 344 vom 16. Dezember 2022 - VD Tribunal cantonal (2022)
DISCOURS DE HAINE, DIFFAMATION, PEINE PRIVATIVE DE LIBERTÉ, ÉGALITÉ ENTRE HOMME ET FEMME | 173 ch. 1 CP, 261bis al. 1 CP, 40 CP, 41 CP